Impact of electric mobility on the design of renewable energy collective self-consumers. (March 2023) - Piazza, Giorgio; Bracco, Stefano; Delfino, Federico; Somma, Marialaura Di; Graditi, Giorgio
Abstract: European countries aim to reach important targets in the energy field through the increase of energy efficiency in final uses, the exploitation of renewable energy sources, and the implementation of energy communities. In the aforesaid framework, renewable energy self-consumers represent a smart solution to foster the adoption of renewable energy power plants and storage systems in the residential and tertiary sectors. The goal of the paper is to propose an optimization-based methodology to evaluate the impact of electric mobility on the optimal design of renewable energy collective self-consumers. The integration of renewable sources and storage systems with charging infrastructures for electric vehicles is analyzed and discussed by running a stochastic optimization model, developed in Matlab/Yalmip, to evaluate different scenarios with different electric mobility penetration levels. The paper shows how the presence of electric vehicles increases the optimal installed size of the RES plants significantly, from 15% up to more than 25%. Moreover, it underlines how the optimal charging system, in terms of type, number, and size of charging stations, is affected by the considered number of electric vehicles but also by the model and thus the characteristics of the electric vehicles such as the maximum accepted charging power in AC and DC modes.